Status and Prospects of Robotic Gastrectomy for Gastric Cancer: Our Experience and a Review of the Literature - Sejin Lee; Taeil Son; Hyoung-Il Kim; Woo Jin Hyung (Gastroenterology Research and Practice)
Since the first report of robotic gastrectomy, experienced laparoscopic surgeons have used surgical robots to treat gastric cancer and resolve problems associated with laparoscopic gastrectomy. However, compared with laparoscopic gastrectomy, the superiority of robotic procedures has not been clearly proven. There are several advantages to using robotic surgery for gastric cancer, such as reduced estimated blood loss during the operation, a shorter learning curve, and a larger number of examined lymph nodes than conventional laparoscopic gastrectomy. The increased operation time observed with a robotic system is decreasing because surgeons have accumulated experience using this procedure. While there is limited evidence, long-term oncologic outcomes appear to be similar between robotic and laparoscopic gastrectomy. Robotic procedures have a significantly greater financial cost than laparoscopic gastrectomy, which is a major drawback. Recent clinical studies tried to demonstrate that the benefits of robotic surgery outweighed the cost, but the overall results were disappointing. Ongoing studies are investigating the benefits of robotic gastrectomy in more complicated and challenging cases. Well-designed randomized control trials with large sample sizes are needed to investigate the benefits of robotic gastrectomy compared with laparoscopic surgery.